The Multilateral System of Payments : Keynes, Convertibility, and the Internationa Monetary Fund's Articles of Agreement - Gold, Joseph (Washington, D.C. : International Monetary Fund, 1981)
Volume 26 of the Collected Writings of John Maynard Keynes records for the first time a strange episode in the development of the International Monetary Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet